Canine Distemper Virus (CDV) in Another Big Cat: Should CDV Be Renamed Carnivore Distemper Virus? - Terio, Karen A. (American Society of Microbiology, 2013)
One of the greatest threats to the conservation of wild cat populations may be dogs or, at least, one of their viruses. Canine distemper virus (CDV), a single-stranded RNA virus in the Paramyxoviridae family and genus Morbillivirus, infects and causes disease in a variety of species, not just canids. An outbreak of CDV in wild lions in the Serengeti, Tanzania, in 1994 was a wake-up call for conservationists, as it demonstrated that an infectious disease could swiftly impact a previously healthy felid population. To understand how this virus causes disease in noncanid hosts, researchers have focused on specific mutations in the binding site of the CDV hemagglutinin gene. Now, Seimon et al. provide information on CDV in its latest feline victim, the endangered wild Amur tiger (Panthera tigris altaica) [T. A. Seimon et al., mBio 4(4):e00410-13, 2013, doi:10.1128/mBio.00410-13]. Their findings of CDV strains infecting tigers, in combination with recent information from other felids, paints a different picture, one in which CDV strains from a variety of geographic lineages and with a variety of amino acid residues in the hemagglutinin gene binding site can infect cats and cause disease. Although CDV has been known as a multihost disease since its discovery in domestic dogs in 1905, perhaps it is time to reconsider whether these noncanid species are not just incidental or “spillover” hosts but, rather, a normal part of the complex ecology of this infectious disease.